Barotropic response of the global atmosphere to large-scale tropical convective forcing - Harris, Katherine A., author (Colorado State University. Libraries, 1999)
A nonlinear shallow water model on the sphere is used to study the effect of largescale tropical convective forcing on the response of the global circulation. Both the spatial and temporal characteristics of the forcing are found to significantly affect the production of tropical and extratropical circulation anomalies. The horizontal shape and location of the convective forcing determines the strength, stability, and symmetry of the upper tropospheric response, the proportion of energy transferred into westward- and eastward-dispersing Rossby modes, and the exact direction of energy propagation. Together, these effects produce teleconnection patterns similar to those observed in the atmosphere. The strongest eastward teleconnection patterns are produced when the convective forcing is meridionally elongated and/or centered off of the Equator. The timescale of the convective forcing determines the distribution of energy into Rossby, Kelvin, and gravity-inertia waves through a filtering on the wave spectrum. An analytical solution to the divergent barotropic vorticity equation is derived to highlight this timescale filter. When the forcing timescale is long, only the longest Rossby waves, with westward group velocities, can be excited at large amplitudes. As the timescale decreases, both the shorter Rossby waves, which have eastward group velocities, and the long gravity waves can be excited. The complete response of a stratified atmosphere is then shown to depend not only on the horizontal shape and timescale of the forcing, but also on its vertical structure. Lower tropospheric convective forcing excites a much more vigorous response in the circulation than does upper tropospheric forcing. Strong cyclonic vortices, which can be likened to tropical cyclones, are generated by the unstable breakdown of the flow in the lower troposphere. The initiation locations and the direction of propagation of these vortices are determined by the horizontal shape and orientation of the convective forcing, through differences in Rossby wave energy dispersion. This reasoning provides a simple explanation for observations that tropical cyclones which form in the Western North Pacific during a "reverse monsoon trough" episode tend to track to the north or northeast (Lander 1996), as opposed to the more climatologically favored northwestward tracks of most Western North Pacific tropical storms.
Spring 1999.
Also issued as author's thesis (M.S.) -- Colorado State University, 1999.
Keywords: Atmospheric circulation; Baroclinicity; Atmospheric turbulence